2017
DOI: 10.1016/j.jadohealth.2016.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Inequitable Gender Norms From Early Adolescence to Young Adulthood in Uganda: Tool Validation and Differences Across Age Groups

Abstract: Young people internalize gender norms about sexual and intimate relationships, and violence, at early ages. Programs to address negative health outcomes should explicitly address inequitable gender norms and more consistently expand to reach younger age groups. In this first application of the GEM Scale among 10- to 14-year-olds, we confirm that it is a valid measure in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 35 publications
(26 reference statements)
10
82
1
1
Order By: Relevance
“…; Vu et al . ). Promoting gender equitable attitudes should start in childhood and continue during the formative period of adolescence and into adulthood.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Vu et al . ). Promoting gender equitable attitudes should start in childhood and continue during the formative period of adolescence and into adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…; Vu et al . ). The general discourse in studies that used the GEM scale in sub‐Saharan Africa (SSA) settings found that both men and women were in high support for gender inequitable norms, with women being less gender equitable (Kazaura et al .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The third strategy is facilitator-led group conversations, where participants look critically at existing norms and practices within their group and renegotiate those norms among themselves. A few models exist of how group reflection processes can help achieve change in harmful social norms [18,20,[61][62][63][64]. Studying effective facilitator-led programmes, Cislaghi [65,66] identified three steps for social norms change: 1) motivation (where participants learn about the detrimental consequences for themselves and others of their compliance with the harmful norm); 2) deliberation (where participants create a new positive norm within their reference group and identify strategies to motivate others in their surroundings); and 3) action (where participants publicly enact their strategies and motivate others to join the group, eventually reaching the critical mass needed for normative change).…”
Section: Introductionmentioning
confidence: 99%